Age, gender, and risk-taking : Evidence from the S&P 1500 executives and market-based measures of firm risk - Peltomäki, Jarkko; Sihvonen, Jukka; Swidler, Steve; Vähämaa, Sami (Wiley, 2021)
This paper contributes to the literature by examining whether the age and gender of the firm's top executives influence market-based measures of firm risk. Using data on the S&P 1500 firms, we document that chief executive officer (CEO) and chief financial officer (CFO) age and gender have a direct effect on market-based firm risk measures in addition to the indirect influence they may have through corporate policy choices. Specifically, we find that firms led by older CEOs and CFOs have less volatile stock returns and lower idiosyncratic risk. Although the relationship between executive gender and firm risk is more equivocal, our results suggest that female-led firms are associated with lower levels of total and idiosyncratic risks after controlling for firm-specific attributes, policy choices, and managerial risk-taking incentives. We also document that CEO and CFO age and gender do not influence the level of systematic risk. Overall, our empirical findings demonstrate that the age and gender of the firm's top executives may have important implications for firm riskiness.
Keywords: age; CEOs; CFOs; executives; firm risk; gender; risk-taking; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|